Non – English majored students’ evaluation of the course book “LIFE” for the General English course at Bac Lieu University : - Dương, Thế Bảo (Trường đại học Cần Thơ, 2018)
This aims of the study were to investigate how non- English majored students evaluate the course book LIFE for their General English Course. In addition, the result of the study proposes a deep insight from non – English majored students’ evaluation of the course book for teachers and administrators to enhance the teaching method and quality of General English Course at the university as well as prose solutions for adoption of the new course book in the future.